Retrospective analysis of medical malpractice claims in tertiary hospitals of China: the view from patient safety - Guohong Li; Yao Yao; Heng Li; Shengjie Dong; Ziyi Liao; Suwei Yuan; Yujie Cui (BMJ Open, 2020)
Objectives The study analysed medical malpractice claims to assess patient safety in hospitals. The information derived from malpractice claims reflects potential risks and could help lead to reducing medical errors and improving patient safety.Design, setting We analysed 4380 medical malpractice claims from 351 grade-A tertiary hospitals in China for 2008–2017. We examined the characteristics of medical errors and patient safety, including the types of medical errors, proportionate liabilities and payments for medical malpractice in different clinical specialties.Main outcome measures We assessed claim characteristics, payment amounts and liability.Results Our data analysis demonstrated that 72.5% of the claims involved medical errors, with average payments of US$31 430. The hospital’s errors in medical malpractice resulted in 41.4% average liability in patient injury payments. Most medical malpractice cases occurred in Shanghai (817 claims, 18.7%) and Beijing (468 claims, 10.7%). The highest risks for medical error and malpractice claims were related to orthopaedics (11.3% of all claims, 72.8% with medical errors) and obstetrics and gynaecology (10.0% of all claims, 76.0% with medical errors). The highest rates related to proportionate liabilities were observed in otolaryngology (51.9%) and endocrinology (47.7%). Respiratory medicine had the highest proportion of claims in death rates (77.3%). Medical technology errors accounted for 91.8% of the claims and medical ethics errors for 5.8%. The highest average payment was found in cardiovascular surgery (US$41 733) and the lowest in stomatology (US$8822).Conclusions A previous study found that grade-A tertiary hospitals in China have similar medical error rates to general Chinese hospitals. 36Different specialties had different risk characteristics regarding medical errors, payments and proportionate liabilities. Orthopaedics had the highest number of malpractices claims and higher proportionate liability but lower death rates.